FAKTOR DETERMINAN YANG MEMPENGARUHI PEMILIHAN PERSALINAN DENGAN DUKUN DI WILAYAH KERJA PUSKESMAS SELAT BARU KECAMATAN BANTAN KABUPATEN BENGKALIS TAHUN 2021 - Heni Heri Yeni; Siska Indrayani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Phenomenon witch doctor baby is wrong one enough part _ big the effect in determine health mother and baby , because about 40% of births babies in Indonesia are helped by witch doctor baby . state this the more aggravated because generally witch doctor baby helping _ labor the no witch doctor trained and habits that sometimes harmful health for woman pregnant and mother post copy . So that Thing this is what makes researcher interested in To do research entitled _ Factor influencing determinant _ election labor with shaman in the Work Area Public health center Strait New Regency Bengkalis . As for destination study this is for knowing influence age , parity , attitude , knowledge , support family and distance to election labor with shaman in the Work Area Public health center New Straits Regency Bengkalis . Method study this with method observational with cross sectional approach . Respondent in study this is mother ever _ To do labor and that includes to in target mother Maternity in the Work Area Public health center New Straits on year 2020. Amount sample taken _ as many as 60 people. Technique taking sample in study this using random sampling. Data analyzed with use chi square test with test regression . Results study show that attitude mother (p=0.000) and Support family (p=0.028) has an effect to election helper childbirth . Whereas factor age (p=0 .33 ), parity (p=0.89), knowledge mother (p=0.43) and distance (p=0.053) no take effect against election helper childbirth . which is factor dominant to alternative election labor is factor attitude mother . Keywords : Election _ helper childbirth , attitude mother , knowledge , age , parity , support family and distance .